The Impact of Cross-Border Banking on Financial Stability - Dirk Schoenmaker; Wolf Wagner (Tinbergen Institute, 2011)
This paper focuses on the stability aspects of cross-border banking. We first argue that cross-border banking brings about various benefits and costs for financial stability. Based on this, we draw conclusions for the desirability of cross-border banking in the EU, and derive implications for its optimal form. Next, we derive metrics that allow quantifying whether cross-border banking in a country (or region) takes a desirable form and apply these metrics to the EU countries. Our results suggest that the countries with the largest banking centers, UK and Germany, are well diversified. By contrast, the New Member States (NMS) are highly dependent on a few West-European banks and thus vulnerable to contagion effects. The Nordic and Baltic regions are also much interwoven without much diversification. At the system-wide level, the EU banking system is weakly diversified, with an overexposure to the US and an underexposure to Japan and China. This explains why the recent US originated financial crisis had such a large impact on European banks.
Keywords: G21; G28; 330; International Banking; Portfolio Diversification; Financial Stability; Bankgeschäft; Internationale Bank; Finanzkrise; Ansteckungseffekt; Welt